PENYULUHAN TENTANG GIZI SEIMBANG PADA SISWA SMK SAHID SURAKARTA - Wardani, Dyah Ayu Kusuma; Kusumawati, Dewi; Prasetyo, Budi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Balanced nutrition is a daily food composition that contains nutrients in types and quantities that suit body's needs, taking into account the principles of food diversity or variety, physical activity, cleanliness and ideal body weight (BB). Aim of this counseling was to increase knowledge and understanding of balanced nutrition among students at Sahid Vocational School, Surakarta. Methods used were lectures and discussions. Media used in this counseling were leaflets and flashcards. Participants in this community service activity were students of SMK Sahid Surakarta class XI TBO 2. Implementation of this counseling received a good response from students with an attendance percentage of 86,7%. Results of community service activity effectiveness could be seen from N-gain value = 0,56 in medium category. Keywords: counseling, balanced nutrition, student, leaflet, flashcard